Pathophysiological Relevance of Renal Medullary Conditions on the Behaviour of Red Cells From Patients With Sickle Cell Anaemia - Lu, David C.-Y.; Wadud, Rasiqh; Hannemann, Anke; Rees, David C.; Brewin, John N.; Gibson, John Stanley (Frontiers in Physiology, 2021)
Red cells from patients with sickle cell anaemia (SCA) contain the abnormal haemoglobin HbS. Under hypoxic conditions, HbS polymerises and causes red cell sickling, a rise in intracellular Ca2+ and exposure of phosphatidylserine (PS). These changes make sickle cells sticky and liable to lodge in the microvasculature, and so reduce their lifespan. The aim of the present work was to investigate how the peculiar conditions found in the renal medulla – hypoxia, acidosis, lactic acid, hypertonicity and high levels of urea – affect red cell behaviour. Results show that the first four conditions all increased sickling and PS exposure. The presence of urea at levels found in a healthy medulla during antidiuresis, however, markedly reduced sickling and PS exposure and would therefore protect against red cell adherence. Loss of the ability to concentrate urine which occurs in sickle cell nephropathy would obviate this protective effect and may therefore contribute to pathogenesis.